Determinants of health-related quality of life in recently detoxified patients with severe alcohol use disorder - Najlaa Lahbairi; Alice Laniepce; Shailendra Segobin; Nicolas Cabé; Céline Boudehent; François Vabret; Géraldine Rauchs; Anne-Lise Pitel (Health and Quality of Life Outcomes, 2022)
Abstract Background Health-related quality of life (HRQoL) is an important clinical outcome in Alcohol Use Disorder (AUD) and is considered as a relevant indicator of treatment success. While a better understanding of the factors affecting HRQoL would enable to adjust patients’ care to favour treatment outcome, the determinants of HRQoL in AUD remain unclear. This study aims at describing HRQoL in AUD patients and at identifying its best predictors. Methods 53 recently detoxified patients with severe AUD (sAUD) underwent a cognitive assessment and filled in a HRQoL questionnaire dedicated to AUD patients (Alcohol Quality of Life Scale; AQoLS), as well as questionnaires concerning socio-demographics, alcohol history, sleep quality, depression, anxiety and impulsivity. 38 healthy controls (HC) underwent the same assessment (except AQoLS) in order to identify the altered cognitive and clinical variables that could potentially be determinants of HRQoL in sAUD. Results sAUD patients reported that alcohol affects their HRQoL mainly in the “negative emotions”, “control”, “relationships”, and “sleep” domains. Compared to HC, they were impaired on episodic memory, working memory, executive functions, and processing speed tasks. They also reported lower sleep quality, higher depression, anxiety and impulsivity. No association was found between AQoLS total score and socio-demographics, cognitive performance, or sleep quality in patients. We found a significant correlation between HRQoL and depression/anxiety as well as impulsivity. Anxiety and impulsivity were indeed the only significant predictors of HRQoL, explaining 47.7% of the variance. Conclusion Anxiety and impulsivity are crucial determinants of HRQoL in recently detoxified sAUD patients. Since anxiety and impulsivity are frequent issues in addiction and especially in AUD, they should be particularly considered by clinicians to favour treatment outcomes.